Neurocysticercosis and epilepsy: Imaging and clinical characteristics - Rodríguez-Leyva, Ildefonso; Cantú-Flores, Karla; Domínguez-Frausto, Arturo; Vaudano, Anna Elisabetta; Archer, John; Bernhardt, Boris; Caciagli, Lorenzo; Cendes, Fernando; Chinvarun, Yotin; Federico, Paolo; Gaillard, William D.; Kobayashi, Eliane; et al. (Epileptic Disorders, 2023)
The ILAE Neuroimaging Task Force aimed to publish educational case reports highlighting basic aspects related to neuroimaging in epilepsy consistent with the educational mission of the ILAE. Neurocysticercosis (NCC) is highly endemic in resource-limited countries and increasingly more often seen in non-endemic regions due to migration. Cysts with larva of the tapeworm Taenia solium lodge in the brain and cause several neurological conditions, of which seizures are the most common. There is great heterogeneity in the clinical presentation of neurocysticercosis because cysts vary in number, larval stage, and location among patients. We here present two illustrative cases with different clinical features to highlight the varying severity of symptoms secondary to this parasitic infestation. We also present several examples of imaging characteristics of the disease at various stages, which emphasize the central role of neuroimaging in the diagnosis of neurocysticercosis.
CRIS-Team Scopus Importer:2023-05-05
Keywords: CT; epilepsy; MRI; neurocysticercosis; neuroimaging